Assessing Employees' Perceptions of Green Banking in Nepal's Commercial Banks - Ojha, Shristi Suman (Apex Journal of Business and Management, 2025)
This study aimed to explore employees' perceptions of green banking in commercial banks of Nepal, focusing on the influence of five key independent variables: green financial products and services, green human resource management, green investment, risk management, and green business strategies. Data were collected from 386 respondents using a structured questionnaire. The relationships between the independent variables and employees' perceptions of green banking were analyzed using the Statistical Package for Social Science (SPSS) software. Descriptive analysis, correlation, and regression techniques were employed to interpret the data. The empirical findings revealed that green financial products and services, green investment, and green business strategies have a significant positive relationship with employees' perceptions of green banking. These factors play a crucial role in shaping employees' views on green banking initiatives, underscoring the importance of offering sustainable financial products, investing in eco-friendly projects, and adopting green business practices within commercial banks. Conversely, the study found that green human resource management and risk management do not exhibit a significant relationship with employees' perceptions of green banking. The study emphasizes that commercial banks should prioritize enhancing green financial products, green investment, and green business strategies to improve employees' perceptions of green banking.